The winter orphans - Beck, Kristin, 1979- (Berkley, 2022)
"A poignant and ultimately triumphant novel based on the incredible true story of children who braved the formidable danger of guarded wintry mountain passes in France to escape the Nazis. Southern France, 1942 In a remote corner of France, Jewish refugee Ella Rosenthal has finally found a safe haven. It has been three years since she and her little sister, Hanni, left their parents to flee Nazi Germany, and they have been pursued and adrift in the chaos of war ever since. Now, they shelter among a hundred other young refugees in a derelict castle overseen by the Swiss Red Cross. Swiss volunteers Rösli Näf and Anne-Marie Piguet uphold a common mission: to protect children in peril. Rösli, a stubborn and resourceful nurse, directs the colony of Château de la Hille, and she has created a thriving community against all odds. Anne-Marie, raised by Swiss foresters, becomes both caretaker and friend to the children, and she vows to do whatever is necessary to keep them safe. However, when Germany invades southern France, safeguarding Jewish refugees becomes impossible. Château de la Hille faces unrelenting danger, and Rösli and Anne-Marie realize that the only way to protect the eldest of their charges is to smuggle them out of France. Relying on Rösli's fierce will and Anne-Marie's knowledge of secret mountain paths, they plot escape routes through vast Nazi-occupied territory to the distant border. Amid staggering risk, Ella and Hanni embark on a journey that, if successful, could change the course of their lives and grant them a future"--